Neutron star characteristics from the neutron structure - Annila, Arto (Frontiers in Physics, 2023)
We draw insight into neutron star structure and characteristics from the neutron structure. The eigenvectors of the special unitary group, SU(3), describing baryons, imply that neutron quarks reside on three faces of a tetrahedron. The tetrahedral structure accounts for the neutron magnetic moment and mass. Thus, we reason that neutrons precipitate with aligned magnetic moments into the triakis truncated tetrahedron tesselation under immense gravitational pressure. Since the particle's tetrahedral symmetry does not match the crystal's rhombic symmetry, the total magnetic moment invariably misaligns with the star's spinning axis. We infer further from the neutron structure that with increasing gravitational pressure, two neutrons condense into the same tetrahedron. Due to doubling density, the contracting star spins up abruptly but then settles down slowly as the gradients in density smoothen. Since down quarks are positioned for pairwise fusions into anti-up quarks in the dineutron, we reason that tetraquark indeed forms as gravitational pressure increases further. Accompanying loss of mass, the star counterbalances by spinning down suddenly but recovering as the gradients in density smoothen again. Ultimately, when gravitational pressure increases even more, the anti-up quarks will annihilate with up quarks. As the core becomes ever more structured, such high-energy events fade out, and eventually, only magnetic field-collimated radio-frequency dissipation drives the spin down. The nuclear moments manifest fully in a magnetar, free from floating, hence counteraligning baryonic matter. In conclusion, the neutron structure makes sense of the neutron star density, magnetism, beams at an angle to the spinning axis, and pulsing transients and paves the way for making sense of reactions in a black hole.